Penduduk pribumi dalam politik pertolongan bencana Krakatau 1883 - Tantri, Erlita (Jurnal Kependudukan Indonesia, 2013)
The eruption of Krakatau on August 26 to 27, 1883 was one of the largest and strongest volcanic eruption in the 19th century after Tambora Mountain in 1815. The eruption of Krakatau in 1883 led to a large number of casualties and severe damage to both the environment and the people and government infrastructure as a result of the eruption of volcanic material and the tsunami waves. The information of the eruption and its effects spread all over the world and generated both attention and donations for the victims. In undulating relief from the archipelago and the international community poured into the disaster relief fund administered by the Dutch colonial government. However, how was the implementation of the post-disaster relief assistance administered by the Dutch government, especially concerning the local residents who were the biggest victims in the eruption of Krakatau? How effective was the management of the disaster relief funds organized by the Dutch government? Through the study of literature with the resources from the Krakatau's disaster assistance report written by the Dutch and famous verses of the local population as references, this paper would like to see the effectiveness of the Dutch colonial political disaster, especially in the event of Krakatau's eruption in Banten and Lampung.